Orally bioavailable amine-linked macrocyclic inhibitors of factor XIa. Issue 4 (15th February 2020) - Fang, Tianan; Corte, James R.; Gilligan, Paul J.; Jeon, Yoon; Osuna, Honey; Rossi, Karen A.; Myers, Joseph E.; Sheriff, Steven; Lou, Zhen; Zheng, Joanna J.; Harper, Timothy W.; Bozarth, Jeffrey M.; et al.
Graphical abstract: Abstract: The discovery of orally bioavailable FXIa inhibitors has been a challenge. Herein, we describe our efforts to address this challenge by optimization of our imidazole-based macrocyclic series. Our optimization strategy focused on modifications to the P2 prime, macrocyclic amide linker, and the imidazole scaffold. Replacing the amide of the macrocyclic linker with amide isosteres led to the discovery of substituted amine linkers which not only maintained FXIa binding affinity but also improved oral exposure in rats. Combining the optimized macrocyclic amine linker with a pyridine scaffold afforded compounds 23 and 24 that were orally bioavailable, single-digit nanomolar FXIa inhibitors with excellent selectivity against relevant blood coagulation enzymes.